The Influence of Online Reviews and Content Creators on Purchasing Decisions for Smartphone Products - Asnusa, Soraya; Arta, Farrel; Purnomo, Ari (International Conference on Digital Business Innovation and Technology Management (ICONBIT), 2024)
The development of information and communication technology, especially the internet, has changed the way consumers search for information and make purchasing decisions. This can be seen from the increasing number of consumers who use online reviews and content creators as a source of information before buying smartphone products. This study aims to analyze the effect of online reviews and content creators on purchasing decisions for smartphone products. The results showed that online reviews and content creators have a positive and significant influence on purchasing decisions for smartphone products. Online reviews provide detailed information about the product, while content creators provide recommendations and testimonials that can help consumers in making a purchase decision. This study provides important implications for marketers and smartphone business people. First, it is important to pay attention to online reviews and content creators in building a marketing strategy. Second, it is necessary to build a good relationship with the content creator to get positive reviews and recommendations.